Microstructure, permeability and mechanical properties of accelerated shotcrete at different curing age. (1st March 2015) - Wang, Jiabin; Niu, Ditao; Ding, Sha; Mi, Zelong; Luo, Daming
Highlights: High w / b and volume of fly ash prolonged the setting time of pastes with accelerator. Hydration process of accelerated shotcrete was studied by using XRD, TG–DSC and SEM. It had good correlation between pore structure and permeability of shotcrete after curing 90 d. The model was established of shotcrete in term of w / b, fly ash and curing age. The relationship between strength and pore structure or permeability was discussed. Abstract: Given the different hydration processes of ordinary concrete, shotcrete with low-alkali accelerator not only has short final setting time and high early age mechanical properties but also different hydration products. Shotcrete microstructure was studied at different curing ages by X-ray diffraction, thermogravimetry–differential scanning calorimetry, and scanning electron microscopy to investigate its hydration process. The pore structure and permeability of shotcrete were also tested. The mechanical properties of shotcrete were then studied. Results showed that under the effect of accelerator, the retarded action of gypsum disappeared in the cement–accelerator–water system. C3 A hydrated quickly to form calcium aluminate hydrate (CAH) crystals, and a mesh structure was formed by ettringite, albite, and CAH. A large amount of hydration heat improved the hydration rate of the cement clinker mineral and the density, thus leading to high mechanical properties at the early curing age. The setting time of pastes increased with increasing water–binder ratio and fly ash (FA) dosage. Thus, the hydration process and the microstructure and morphology of the hydration products changed. Excessive water and FA increased the percentage of pores in shotcrete, which directly caused poor permeability. The permeability and compressive strength were poor when the FA dosage was 30% compared with that of 20%. Based on the investigation, a simple 0.5 power relationship between compressive strength and splitting tensile strength of mixture S2, meanwhile, there was an exponential relationship between mechanical performance and permeability or porosity, respectively.